2020
DOI: 10.1093/neuonc/noaa067
|View full text |Cite|
|
Sign up to set email alerts
|

Proton and carbon ion radiotherapy in skull base chordomas: a prospective study based on a dual particle and a patient-customized treatment strategy

Abstract: Background The aim of this study is to evaluate results in terms of local control (LC), overall survival (OS), and toxicity profile and to better identify factors influencing clinical outcome of skull base chordoma treated with proton therapy (PT) and carbon ion radiotherapy (CIRT). Methods We prospectively collected and analyzed data of 135 patients treated between November 2011 and December 2018. Total prescription dose in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 43 publications
1
66
0
Order By: Relevance
“…Cyclin D-dependent kinases (CDK4 and CDK6) are another target for chordoma molecular therapy. These oncoproteins regulate cell cycle progression through the G1 phase into the S phase and have been shown to be overexpressed in chordoma cell lines and tissue samples due to loss of the CDKN2A gene and its protein product, p16INK4a [ 100 ]. Palbociclib, a CDK4/6 inhibitor, has been demonstrated to have in vitro [ 99 , 100 ] efficacy against chordoma cells and is part of a Phase II trial for advanced chordoma and other tumors (NCT03110744, accessed on 31 January 2021) ( Figure 4 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Cyclin D-dependent kinases (CDK4 and CDK6) are another target for chordoma molecular therapy. These oncoproteins regulate cell cycle progression through the G1 phase into the S phase and have been shown to be overexpressed in chordoma cell lines and tissue samples due to loss of the CDKN2A gene and its protein product, p16INK4a [ 100 ]. Palbociclib, a CDK4/6 inhibitor, has been demonstrated to have in vitro [ 99 , 100 ] efficacy against chordoma cells and is part of a Phase II trial for advanced chordoma and other tumors (NCT03110744, accessed on 31 January 2021) ( Figure 4 ).…”
Section: Treatmentmentioning
confidence: 99%
“…In a recent publication on skull base chordomas treated at CNAO, Iannalfi et al. found that 92% of the local recurrences were attributable to suboptimal target dose in regions close to the brainstem or optic pathways ( 19 ). The estimated 5-year local control (LC) rate was 71%.…”
Section: Discussionmentioning
confidence: 99%
“…In the large majority of particle therapy series, gross tumor volume correlated with local control, and patients with small residual disease had a better outcome [ 22 , 24 , 26 29 , 36 , 37 ]. Moreover, several series demonstrated a correlation between compression of brainstem and/or optic pathways and outcome [ 26 , 29 , 34 ]. Finally, target coverage emerged as another factor strongly predictive of outcome [ 23 , 27 , 29 , 37 ].…”
Section: Future Developmentsmentioning
confidence: 99%
“…Moreover, several series demonstrated a correlation between compression of brainstem and/or optic pathways and outcome [ 26 , 29 , 34 ]. Finally, target coverage emerged as another factor strongly predictive of outcome [ 23 , 27 , 29 , 37 ].…”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation